Post-operative physiotherapy in breast cancer surgery: a bibliographic review (Research, Society and Development, 2023)
Breast cancer occupies the second position among the most common types of cancer in the world, being more common among women and its incidence has been increasing over time, in this way, physical therapy comes to add to this postoperative treatment process. of breast cancer, in order to improve the quality of life of patients. The objective of this work is to analyze the physiotherapeutic view in the postoperative period of patients with breast cancer, in order to expose ways to improve the quality of life of patients and show the importance of physiotherapy in the oncological environment that grows more every day, through a bibliographic review. This literature review is an exploratory-descriptive research. To build a theoretical framework, databases of scientific publications were searched in electronic databases in the online public domain, such as PubMed, SciElo, and Science Direct. Open access scientific articles in Portuguese and English were selected, researched from 06/20/2022 to 10/9/2022. There is no consensus on the range of motion of the shoulder in the first postoperative days, so there are different forms of rehabilitation for these patients undergoing conservative surgery for malignant breast cancer, and in this way I intervened in the possible complications caused by this procedure. Based on the articles studied, physiotherapy proved to be very important for these patients undergoing these surgeries, which clearly interfere with their well-being, self-esteem and psychological.